Numerical Solution of Homogeneous One-Dimensional Heat Equation Using Crank-Nicolson Method - Faizzuddin Jamaluddin; Ahmad Danial Hidayatullah Badrolhisam; Muhammad Arif Hannan Mohamed; Muhammad Aniq Qayyum Mohamad Sukry; Norazlina Subani (Universiti Sains Islam Malaysia, 2024)
E-Proceeding: Insan Junior Researcher International Conference (iJURECON) 2020 Date: 17-18 November 2020 Organized by: Kolej Genius Insan Virtual Conference Page:25-31